Fat compartments in patients with depression: a meta-analysis - Cosan, Alisa Susann; Schweiger, Julietta U.; Kahl, Kai G.; Hamann-Weber, Bettina; Deuschle, Michael; Schweiger, Ulrich; Westermair, Anna L. (Brain and behavior, 2021)
Introduction Depressive disorders are a common illness worldwide. Major depression is known as a significant predictor of the metabolic syndrome. However, the effects of depression on adipose tissue compartments are controversial. This meta-analysis aimed to evaluate the state of research on the relationship between patients with depression and adipose tissue compartments as compared to nondepressed individuals. Methods The PubMed database was searched for human studies that measured adipose tissue compartments such as visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT) and/or organ-specific adipose tissue measurements using dual-energy X-ray absorptiometry, magnetic resonance imaging or computed tomography scan and reported the means and a measure of variance separately for depressed individuals and healthy controls. Twelve articles were identified, including a total of 1,141 depressed and 2,545 nondepressed individuals. Results Major depressive disorder and self-reported depressive symptoms were associated with elevated visceral adipose tissue and elevated subcutaneous adipose tissue. Subanalyses for gender, age, method of adipose tissue measurement, and method of depression assessment showed elevated visceral adipose in depressed individuals. The results could be replicated when focussing on studies controlling for body mass index (BMI). Regarding other adipose tissue compartments, meta-analysis could not be carried out due to lack of studies. Conclusions Depression is associated with enlarged visceral and subcutaneous adipose tissue. Further, especially longitudinal, research is needed to identify the mechanism through which depressive disorders contribute to visceral adiposity.
Gesehen am 23.06.2021